Use triangle ABC drawn below & only the sides labeled. Find the side of length AB in terms of side a, side b & angle C only. You will need to use both Soh-Cah-Toa and the Pythagorean Theorem to solve for side AB.

Use triangle ABC drawn below amp only the sides labeled Find the side of length AB in terms of side a side b amp angle C only You will need to use both SohCahTo class=

Respuesta :

Answer:

[tex]AB = \sqrt{a^2 + b^2-2abCos\ C}[/tex]

Step-by-step explanation:

Given:

The above triangle

Required

Solve for AB in terms of a, b and angle C

Considering right angled triangle BOC where O is the point between b-x and x

From BOC, we have that:

[tex]Sin\ C = \frac{h}{a}[/tex]

Make h the subject:

[tex]h = aSin\ C[/tex]

Also, in BOC (Using Pythagoras)

[tex]a^2 = h^2 + x^2[/tex]

Make [tex]x^2[/tex] the subject

[tex]x^2 = a^2 - h^2[/tex]

Substitute [tex]aSin\ C[/tex] for h

[tex]x^2 = a^2 - h^2[/tex] becomes

[tex]x^2 = a^2 - (aSin\ C)^2[/tex]

[tex]x^2 = a^2 - a^2Sin^2\ C[/tex]

Factorize

[tex]x^2 = a^2 (1 - Sin^2\ C)[/tex]

In trigonometry:

[tex]Cos^2C = 1-Sin^2C[/tex]

So, we have that:

[tex]x^2 = a^2 Cos^2\ C[/tex]

Take square roots of both sides

[tex]x= aCos\ C[/tex]

In triangle BOA, applying Pythagoras theorem, we have that:

[tex]AB^2 = h^2 + (b-x)^2[/tex]

Open bracket

[tex]AB^2 = h^2 + b^2-2bx+x^2[/tex]

Substitute [tex]x= aCos\ C[/tex] and [tex]h = aSin\ C[/tex] in [tex]AB^2 = h^2 + b^2-2bx+x^2[/tex]

[tex]AB^2 = h^2 + b^2-2bx+x^2[/tex]

[tex]AB^2 = (aSin\ C)^2 + b^2-2b(aCos\ C)+(aCos\ C)^2[/tex]

Open Bracket

[tex]AB^2 = a^2Sin^2\ C + b^2-2abCos\ C+a^2Cos^2\ C[/tex]

Reorder

[tex]AB^2 = a^2Sin^2\ C +a^2Cos^2\ C + b^2-2abCos\ C[/tex]

Factorize:

[tex]AB^2 = a^2(Sin^2\ C +Cos^2\ C) + b^2-2abCos\ C[/tex]

In trigonometry:

[tex]Sin^2C + Cos^2 = 1[/tex]

So, we have that:

[tex]AB^2 = a^2 * 1 + b^2-2abCos\ C[/tex]

[tex]AB^2 = a^2 + b^2-2abCos\ C[/tex]

Take square roots of both sides

[tex]AB = \sqrt{a^2 + b^2-2abCos\ C}[/tex]

ACCESS MORE